Modelling single-trial ERP reveals modulation of bottom-up face visual processing by top-down task constraints (in some subjects) - Rousselet, Guillaume A.; Gaspar, Carl M.; Wieczorek, Kacper P.; Pernet, Cyril R. (Frontiers in Psychology, 2011)
We studied how task constraints modulate the relationship between single-trial ERPs and image noise. Thirteen subjects performed two interleaved tasks: on different blocks, they saw the same stimuli, but they discriminated either between two faces or between two colours. Stimuli were two pictures of red or green faces that contained from 10% to 80% of phase noise, with 10% increments. Behavioural accuracy followed a noise dependent sigmoid in the identity task but was high and independent of noise level in the colour task. EEG data recorded concurrently were analyzed using a single-trial ANCOVA: we assessed how changes in task constraints modulated ERP noise sensitivity while regressing out the main ERP differences due to identity, colour and task. Single-trial ERP sensitivity to image phase noise started at about 95-110 ms post-stimulus onset. Group analyses showed a significant reduction in noise sensitivity in the colour task compared to the identity task from about 140 ms to 300 ms post-stimulus onset. However, statistical analyses in every subject revealed different results: significant task modulation occurred in 8/13 subjects, one showing an increase and 7 showing a decrease in noise sensitivity in the colour task. Onsets and durations of effects also differed between group and single-trial analyses: at any time point only a maximum of 4 subjects (31%) showed results consistent with group analyses. We provide detailed results for all 13 subjects, including a shift function analysis that revealed asymmetric task modulations of single-trial ERP distributions. We conclude that, during face processing, bottom-up sensitivity to phase noise can be modulated by top-down task constraints, in a broad window around the P2, at least in some subjects.